PENGARUH INFLASI, NILAI TUKAR RUPIAH DAN SUKU BUNGA BI TERHADAP INDEKS HARGA SAHAM INFOBANK15 PADA BEI - Ratih Nariwanti Anggraeni; Lia Nirawati (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
This research aims to determine the simultaneous and partial influence of Inflation, Rupiah exchange rate, and Bank Indonesia interest rate against Infobank15 Index on Indonesia Stock Exchange period 2016 – 2021. This study uses secondary data in the form of summary of monthly index reports obtained from financial websites. The population in this study is a time series data that amounts to 60 months and starts from August 2016 to July 2021 by determining samples using saturated samples. The data was analyzed using multiple linear regression analysis techniques. Hypothesis tested using F test and t test. The result showed that simultaneously variable Inflation, Rupiah Exchange Rate, and Bank Indonesia Interest Rate had a significant effect on the Infobank15 Index on the Indonesia Stock Exchange. Partialy Inflation has significant negative effect on Infobank15 Index. Rupiah Exchange Rate has no effect on Infobank15 Index. Bank Indonesia Interest Rate has significant positive effect on Infobank15 Index